Nicholas of Cusa’s Interpretation of the Category of Hidden God on the Basis of the Dialogue De Deo Abscondito (in Polish) (Diametros, 2018)
The paper presents the theological and philosophical category of Deus absconditus (‘hidden God’) and shows it in the perspective of Nicholas of Cusa’s ideas contained in his dialogue De Deo Abscondito. The hidden God is the totally transcendent God that is beyond creation both ontologically and logically. Deus absconditus is God that cannot be the object of rational cognition and positive knowledge, hence the only way to acquire any knowledge of him is the method of negative (apophatic) theology. Therefore, the hidden God is the subject of mystical epistemology. Cusanus’s Deus absconditus is also called Truth (Veritas) and as such he is not only incomprehensible, but also incommunicable. God’s transcendence (I), rational unintelligibility (II) and inexpressibility (apophasis) (III) are the aspects which the considerations presented in this paper build on.
Keywords: Nicholas of Cusa; De Deo Abscondito; hidden God; negative theology; apophatic theology; mystical epistemology; ‘truth’ (veritas)